Analisa Antifungal Ekstrak Etanol Biji Alpukat Terhadap Pertumbuhan Jamur Colletotrichum sp. pada Cabai Rawit (Capsicum Frutescens) - Muhammad Ferdiansyah; Jamilah Nasution; Rosliana Lubis (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2020)
This study aimed to assess the potential of avocado seed extract as an antifungal agent and to determine the optimum concentration of avocado seed extract in inhibiting the growth of Colletotrichum. This research used laboratory- scale experimental methods. Inhibition test of extract towards Colletotrichum was carried out using poison food method using following extract concentration 20%, 40%, 60%, 80% and 100% Topsin M Wp 0.2% were used as negatif control. The result showed that avocado seed extract had a significant antifungal activity against Colletotrichum at the consentration of 40%, the effect was emerged since the 4th day of incubation which was observed by measuring fungal growth diameter